Peningkatan Manajemen Bank Sampah dan Partisipasi Masyarakat melalui Penggunaan Aplikasi Bank Sampah Online pada Bank Sampah Bumi Inspirasi Kota Bandung: Improving Waste Bank Management and Citizen Pariticipation through the Use of the Online Waste Bank Application at Bank Sampah Bumi Inspirasi Bandung City - Melian, Lusi; Fachrizal, Muhammad Rajab; Susilawati, Erna (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The main problems faced by community-based waste banks are the lack of a digitized transaction recording system and low community participation in waste management activities. This Community Service Activity (PKM) aims to implement an online waste bank application to improve the quality of waste bank management and encourage active community participation. The methods used in this activity include socializing about the circular economy and its application concepts, training in using the application, and assisting waste bank managers and customers in using it. The results of the activity show that the online waste bank application can simplify transaction recording, improve the transparency of financial reports, and strengthen management accountability. In addition, community participation has increased, as evidenced by the rise in the number of active customers and more frequent transactions. Thus, the implementation of the online waste bank application has proven effective in supporting orderly, transparent, and sustainable management while strengthening the application of circular economy principles at the community level.